Evaluation of antioxidant activity of selected seagrasses from Argao, Cebu using ferric ion reducing antoxidant power (FRAP) assay. - Tan, Katrina C. (2015)
Plant species have a myriad uses and focus has been shifted to aquatic plants, particularly seagrasses. Antioxidant activity or the ability to reduce oxidative damage-causing free radicals is one of the characteristics investigated in seagrasses. This study aimed to determine whether local seagrass species exhibited this characteristic and to compare the antioxidant activity across species per concentration of seagrass extract, and across concentrations per species.Cymodocearotundata, Enhalusacoroidesand Thalassiahemprichiiseagrass species were collected from Poblacion, Argao, Cebu and were evaluated for antioxidant activity using the FRAP assay. Aqueous extraction was done for all species and concentrations of 0.5 mg/mL, 1.0 mg/mL and 1.5 mg/mL seagrass extract/water were prepared and subjected to FRAP assayin vitro. UV-Vis spectrophotometry was then done at an absorbance of 623 nm. Absorbance values were then subjected to statistical analysis using SPSS and results showed no significant difference (p < 0.05) between the absorbance values, or antioxidant activity, of the seagrass species per concentration, as well as with the standard used (ascorbic acid). Significant difference was observed only between the lowest and highest concentrations of T. hemprichii and not in C. rotundataand E. acoroides. A significant correlation between absorbance and extract concentration was observed only in T. hemprichii and E. acoroides (R = 0.842; R = 0.663). In conclusion, the subject seagrass species did exhibit antioxidant activity without any seagrass species exhibiting significantly greater activity among the others. Greater concentrations also yielded higher absorbance values and therefore, stronger antioxidant activity.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu